2020
DOI: 10.1186/s12884-020-02892-1
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of telemedicine for pregnant women with gestational diabetes mellitus: an updated meta-analysis of 32 randomized controlled trials with trial sequential analysis

Abstract: Background: Gestational diabetes mellitus (GDM) is now a global health problem. Poor blood glucose control during pregnancy may lead to maternal and neonatal/foetal complications. Recently, the development of information and communication technology has resulted in new technical support for the clinical care of GDM. Telemedicine is defined as health services and medical activities provided by healthcare professionals through remote communication technologies. This study aimed to update the systematic review of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
114
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 125 publications
(122 citation statements)
references
References 35 publications
4
114
0
4
Order By: Relevance
“…Outpatient PNC (30) Outpatient breastfeeding support (24) Inpatient ANC (27) Inpatient childbirth care (34) Inpatient PNC (31) Surgical care (16) Neonatal care (small and sick newborns)…”
Section: Resultsmentioning
confidence: 99%
“…Outpatient PNC (30) Outpatient breastfeeding support (24) Inpatient ANC (27) Inpatient childbirth care (34) Inpatient PNC (31) Surgical care (16) Neonatal care (small and sick newborns)…”
Section: Resultsmentioning
confidence: 99%
“…In order to improve healthcare professionals to monitor patients’ health-related indicators and provide timely medical feedback and guidance to improve the physical and psychological status of patients, website-based systems or mobile terminal devices can be used. In a meta-analysis of 32 randomized controlled trials (RCTs), including 5108 patients with GDM (2581 instructed by telemedicine and 2527 controls), the role of remote communication technologies in improving pregnancy outcome was evaluated [ 206 ]. Most studies were conducted in China (21 studies, 65.6%).…”
Section: The Effects Of Diabetes In Pregnancy On the Newborn Infanmentioning
confidence: 99%
“…Most of the systematic reviews and meta-analyses on the use of TM technologies for diabetes mellitus have demonstrated that TM tools help reduce the HbA1c value in individuals with type I, type II diabetes and GDM [7]. However, the effects of TM on other indices of glucose and pregnancy outcomes in patients with GDM remain uncertain [8].…”
Section: Discussionmentioning
confidence: 99%